The Practice of Money Arisan with an Auction-Based Drawing System in Nagori Perlanaan: A Study in Islamic Economic Law - Siregar, Pani Akhiruddin; Ningtias, Agus; Bancin, Kadri (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
This study examines the practice of money arisan with an auction-based drawing system in Nagori Perlanaan through the lens of Islamic economic law. Money arisan, a form of social financial gathering popular in Indonesia, has evolved into various systems, including auction-based mechanisms. This research explores its unique practices and compliance with Islamic legal principles. Utilizing an empirical legal approach, the study analyzes data collected through field observations and interviews with participants of the money arisan. The legal framework is evaluated based on Islamic jurisprudence (fiqh), supported by Quranic verses and Hadith. The mechanism involves members bidding with the highest monetary offer to win the arisan in each period, starting from the second cycle of 38 total cycles. Winners in earlier cycles receive less money due to bid deductions, while those in later cycles benefit from accumulated funds. The arisan structure includes privileges for the chairman and administrative penalties for withdrawal. While the practice fosters financial cooperation, it introduces elements akin to riba due to unequal benefits and the presence of profit-oriented borrowing among members. This contravenes Islamic principles, which emphasize fairness and mutual benefit in financial transactions. The practice of money arisan with an auction-based system in Nagori Perlanaan, though innovative, is deemed non-compliant with Islamic economic law as it involves elements of riba. Legal reform is necessary to align such practices with Sharia principles.Keywords: Money Arisan, Auction System, Islamic Economic Law, Riba, Financial Practices